A Review: Perbandingan Stabilitas Fisik Tablet Zat Aktif Sintesis dengan Ekstrak Tumbuhan - Fadil Priyangan; Yasmin Nurfitriyanti; Cantika Abelya Febrien Wijaya; Sulton Farrel Nuruddin; Najwa Trisari; Rifqi Muhammad Hajid; Ghefira Najwa Akmila (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Tablets are one of the most widely used pharmaceutical dosage forms because they offer various advantages, such as accurate dosing, ease of use, practicality in storage and distribution, and good stability compared to other dosage forms. The physical stability of tablets is a critical factor in ensuring the quality, safety, and efficacy of medications. In the pharmaceutical industry, the active ingredients used in tablet formulations can be derived from synthetic compounds or natural sources, such as plant extracts. This study was conducted to compare the physical stability of tablets containing synthetic active ingredients and tablets containing plant extract active ingredients. This study employed a literature review method with a descriptive-comparative approach. The results showed that tablets formulated using the wet granulation method with synthetic active ingredients exhibited consistent values for hardness, friability, and disintegration time regarding physical stability. In contrast, tablets with a plant extract active ingredients showed more variable results because the characteristics of natural materials can affect the physical stability of the tablets. Therefore, tablets with synthetic active ingredients demonstrated better physical stability compared to herbal extract tablets because the properties of synthetic active substances are more homogeneous and easier to formulate using the wet granulation method.